Daya proteksi minyak atsiri bunga kenanga (Cananga odorata ) dalam sediaan lotion antinyamuk terhadap Aedes aegypti - Puspita, Putu Ayudina Asti; Arpiwi, Ni Luh; Sudatri, Ni Wayan (Jurnal Biologi Udayana; Vol 26 No 2 (2022): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2022.v26.i02.p12, 2022)
Various alternatives have been made to reduce the population of the Aedes aegypti mosquito that caused dengue fever, including the use of mosquito repellent lotions had contained DEET. To reduce the risks and negative impacts of mosquito repellent lotions contained DEET, one of the solutions was to use ylang ylang ( Cananga odorata ) essential oil as a natural mosquito repellent. This studied aims to obtain an anti-mosquito lotion formula with the active ingredient of ylang ylang essential oil and to determine the protection ability of ylang ylang essential oil as an insect repellent to Aedes aegyti . This study aims to determine the yield of ylang flower essential oil, to analyze the concentration of essential oil in lotion that provide the highest protection against Ae. aegypti , to analyze the preference  of the respondents for the lotion formulation, and to determine whether there is sensitivity after using lotion containing ylang flower essential oil. Cananga essential oil in this study was obtained by steamed distillation which was then used as an anti-mosquito agent in lotion preparations. The average yield of ylang flower essential oil with three replications followed by the standard deviation (SD) was 0.63% ± 1.38 w/w. The highest protection ability of mosquito repellent lotion was F3 lotion with 5% essential oil. Lotion F3 in the first hour provided a protection ability of 96.3%, the second hour was 92.3%, and the third hour was 87% and decreased until the sixth hour to 75%. The most preferred formulation by respondents was lotion with 5% ylang – ylang essential oil. After used the anti-mosquito lotion, there was no sticky feeling on the skin and there were no symptoms of sensitivity.